Alternative splicing of FBP-interacting repressor coordinates c-Myc, P27Kip1/cyclinE and Ku86/XRCC5 expression as a molecular sensor for bleomycin-induced DNA damage pathway - Rahmutulla, Bahityar (Impact Journals LLC, 2013)
The far-upstream element-binding protein-interacting repressor (FIR) is a c-myc transcriptional suppressor. FIR is alternatively spliced to lack the transcriptional repression domain within exon 2 (FIRΔexon2) in colorectal cancers. FIR and FIRΔexon2 form homo- or heterodimers that complex with SAP155. SAP155, a subunit of the essential splicing factor 3b subcomplex in the spliceosome, is required for proper P27Kip1 pre-mRNA splicing, and P27Kip1 arrests cells at G1. In contrast, FIR was co-immunoprecipitated with Ku86 and DNA-PKcs. siRNA against Ku86/Ku70 decreased FIR and P27Kip1 expression, whereas siRNA against FIR decreased Ku86/XRCC5 and P27Kip1 expression. Thus the mechanical interaction of FIR/FIRΔexon2/SAP155 bridges c-myc and P27Kip1 expression, potentially integrates cell-cycle progression and c-myc transcription in cell. Bleomycin (BLM) is an anticancer agent that introduces DNA breaks. Because DNA breaks generate the recruitment of Ku86/Ku70 to bind to the broken DNA ends, the possible involvement of FIR and Ku86/Ku70 interaction in the BLM-induced DNA damage repair response was investigated in this study. First, BLM treatment reduced SAP155 expression and increased FIR and FIRΔexon2 mRNA expression as well as the ratio of FIRΔexon2:FIR in hepatoblastoma cells (HLE and HLF). Second, FIR or FIRΔexon2 adenovirus vectors (Ad-FIR or Ad-FIRΔexon2) increased Ku86/Ku70 and P27Kip1 expression in vitro. Third, BLM decreased P27Kip1 protein expression, whereas increased P27Kip1 and γH2AX expression with Ad-FIRΔexon2. Together, the interaction of FIR/SAP155 modulates FIR splicing and involves in cell-cycle control or cell fate via P27Kip1 and c-myc in BLM-induced DNA damage pathway. This novel function of FIR splicing will contribute to clinical studies of cancer management through elucidating the mechanical interaction of FIR/FIRΔexon2/SAP155 as a potential target for cancer treatment.